Experimental Investigation of Wave Pressure Spreading at Gas-Impulse Regeneration of Well Filters - V. V. Ivashechkin; V. V. Veremenuk; A. N. Kondratovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper provides a methodology and experimental investigation results of the process pertaining to pressure impulse spreading due to an underwater explosion of hydrogen-oxygen gas mixture in a cylindrical chamber which is open from the bottom, closed cylindrical and spherical chambers with elastic covers. Comparison of the experimental investigation results with theoretical calculations is given in the paper.